Novel Zinc(II) Complexes of Heterocyclic Ligands as Antimicrobial Agents: Synthesis, Characterisation, and Antimicrobial Studies - Ramesh S. Yamgar; Y. Nivid; Satish Nalawade; Mustapha Mandewale; R. G. Atram; Sudhir S. Sawant (Bioinorganic Chemistry and Applications)
The synthesis and antimicrobial activity of novel Zn(II) metal complexes derived from three novel heterocyclic Schiff base ligands 8-[(Z)-{[3-(N-methylamino)propyl]imino}methyl]-7-hydroxy-4-methyl-2H-chromen-2-one, 2-[(E)-{[4-(1H-1,2,4-triazol-1-ylmethyl)phenyl]imino}methyl]phenol, and (4S)-4-{4-[(E)-(2-hydroxybenzylidene)amino]benzyl}-1,3-oxazolidin-2-one have been described. These Schiff base ligands and metal complexes are characterised by spectroscopic techniques. According to these data, we propose an octahedral geometry to all the metal complexes. Antimicrobial activity of the Schiff base ligand and its metal complexes was studied against Gram negative bacteria: E. coli and Pseudomonas fluorescens, Gram positive bacteria: Staphylococcus aureus, and also against fungi, that is, C. albicans and A. niger. Some of the metal complexes show significant antifungal activity (MIC < 0.2 μg/mL). The “in vitro” data has identified [Zn(NMAPIMHMC)2]·2H2O, [Zn(TMPIMP)2]·2H2O, and [Zn(HBABO)2]·2H2O as potential therapeutic antifungal agents against C. albicans and A. niger.